Information technology for the elderly in times of COVID-19 (Research, Society and Development, 2020)
Experience report that aims to describe an information and communication technology about the elderly with dementia for caregivers in times of COVID-19. It is an extension project with a descriptive typology, like an experience report, developed at Universidade Federal Fluminense. This report is presented according to the following points: the blog and its development, its dissemination page as an extension project and its interfaces. This technology aims at interactivity, dissemination and debate of information that are sources of updating on research and specificities of nursing care for the elderly based on guidelines on hygiene and comfort care for family members and caregivers aiming at prevention in times of COVID-19 when elderly and family members must be in social isolation.